Effect of Different Adhesion Protocols on the Shear Bond Strength of Universal Adhesive Systems to Sound and Artificial Caries-Affected Dentin - Sami, Omnia M.; Naguib, Essam A.; Afifi, Rasha H.; Nagi, Shaymaa M. (European Journal of General Dentistry, 2021)
Objective Bonding to different dentin substrates influences resin composite restoration outcomes. This study investigated the influence of different adhesion protocols on the shear bond strength of universal adhesive systems to sound and artificial caries-affected dentin (CAD).Materials and Methods Occlusal enamel of 80 premolars were wet grinded to obtain flat midcoronal dentin. Specimens were equally divided according to the substrate condition: sound and CAD by subjecting to pH-cycling for 14 days. Each dentin substrate was bonded with the adhesive systems used in this study: Single Bond universal adhesive or Prime&Bond universal (applied either in etch-and-rinse or self-etch adhesion protocol). Adhesive systems were utilized according to manufacturers’ instructions, then resin composite was built up. Specimens were tested for shear bond strength. The data were analyzed by three-way analysis of variance, and failure modes were determined using stereomicroscope.Results There was no statistically significant difference between the two tested adhesive systems on artificially created CAD with different adhesion protocols. On sound dentin, Single Bond universal, either in the etch-and-rinse or self-etch adhesion protocols, revealed higher statistically significant shear bond strength mean values compared with CAD.Conclusion Single Bond universal adhesive in an etch-and-rinse adhesion protocol improved only bonding to sound dentin, while no added positive effect for the etching step with Prime&Bond universal adhesive was found when bonded to both sound and CAD substrates. The influence of CAD on the performance of the universal adhesives was material-dependent.
Keywords: caries-affected dentin; microshear; multimode; universal dental adhesives; adhesion protocols